Edukasi Masyarakat Sebagai Upaya Peningkatan Pemahaman Mengenai Thaharah Bagi Muslimat Desa Kebonrejo Kediri - Jian Nurus Shofa; Miksan Ansori (LP3M IAIFA Kediri, 2022)
The decline of science in Islam was marked by the division of power and empire in the 12th century to the 18th century.